Development and application of a novel cervical lymph collection method to assess lymphatic transport in rats - Hoang, Thu A.; Cao, Enyuan; Gracia, Gracia; Nicolazzo, Joseph A.; Trevaskis, Natalie L. (Frontiers in Pharmacology, 2023)
Background: Fluids, solutes and immune cells drain from the brain and surrounding structures to the cervical lymph vessels and nodes in the neck via meningeal lymphatics, nasal lymphatics and/or lymphatic vessels associated with cranial nerves. A method to cannulate the efferent cervical lymph duct for continuous cervical lymph fluid collection in rodents has not been described previously and would assist in evaluating the transport of molecules and immune cells from the head and brain via the lymphatics in health or disease. Aim: To develop a novel method to cannulate and continuously collect lymph fluid from the cervical lymph duct in rats and to analyze the protein, lipid and immune cell composition of the collected cervical lymph fluid. Methods: Male Sprague-Dawley rats were cannulated at the carotid artery with or without cannulation at the cervical lymph duct. Samples of blood, whole lymph and isolated lipoprotein fractions of lymph were collected and analyzed for lipid and protein composition using commercial kits. Whole lymph samples were centrifuged and isolated pellets were stained and processed for flow cytometry analysis of CD3+, CD4+, CD8a+, CD45R+ (B220) and viable cell populations. Results: Flow rate, phospholipid, triglyceride, cholesterol ester, free cholesterol and protein concentrations in cervical lymph were 0.094 ± 0.014 mL/h, 0.34 ± 0.10, 0.30 ± 0.04, 0.07 ± 0.02, 0.02 ± 0.01 and 16.78 ± 2.06 mg/mL, respectively. Protein was mostly contained within the non-lipoprotein fraction but all lipoprotein types were also present. Flow cytometry analysis of cervical lymph showed that 67.1 ± 7.4% of cells were CD3+/CD4+ T lymphocytes, 5.8 ± 1.6% of cells were CD3+/CD8+ T lymphocytes, and 10.8 ± 4.6% of cells were CD3-/CD45R+ B lymphocytes. The remaining 16.3 ± 4.6% cells were CD3-/CD45- and identified as non-lymphocytes. Conclusion: Our novel cannulation method enables quantitative analysis of the lymphatic transport of immune cells and molecules in the cervical lymph of rats for the first time. This valuable tool will enable more detailed quantitative analysis of changes to cervical lymph composition and transport in health and disease, and could be a valuable resource for discovery of biomarkers or therapeutic targets in future studies.